Биоразлагаемые полимерные композиции с остеогенным потенциалом; Бюллетень сибирской медицины; Т. 19, № 4 - Лебедев С. М. Сергей Михайлович; Чистохин Д. М. Дмитрий Михайлович; Щаденко С. В. Сергей Владимирович; Дзюман А. Н. Анна Николаевна; Николаева О. О. Ольга Олеговна; Митриченко Д. В. Дмитрий Владимирович; Просолов А. Б. Александр Борисович; Хлусов И. А. Игорь Альбертович (2020, 2020)
Заглавие с экрана